Adaptation of Home Falls and Accidents Screening Tool (HOME FAST) as a Fall Risk Screening Tool for the Elderly in First Level Health Facilities at Purworejo Regency - Dewi Susilowardani; Wahyudi Istiono; I Dewa Putu Pramantara (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
Background: The Home Falls and Accidents Screening Tool (HOME FAST) is used for early detection of unsafe environmental conditions at home and risk factors for falls in the elderly. However, in Indonesia there are no data on the adaptation of this instrument. Objective: To determine if the HOME FAST adaptation can be used as a screening tool for the risk of falling in the elderly in the First Level Health Facilities/Fasilitas Kesehatan Tingkat Pertama (FKTP) of Purworejo Regency. Methods: This research was a quantitative study with a cross-sectional design. Subjects were elderly with age over 65 years in the Puskesmas Loano working area that met the inclusion and exclusion criteria. Results: After the adaptation of the HOME FAST instrument was completed, a validity test was performed and a r table result of 0.361 was obtained, indicating all questions were valid. Reliability testing using the Cronbach Alpha formula obtained 0.8461. Subjects were 300 respondents with a distribution of 135 men (45%) and 165 women (55%). The results of the bivariate analysis found three factors that were statistically significantly related, namely gender, age, and the total score of the HOME FAST adaptation instrument. Gender was statistically significantly correlated with a history of falls p = 0.045 (95% CI 2.14-2.56) with RP 1.57 while age was significant with p = 0.046 with (95% CI: 2.85-3.46), and the risk of unsafe total HOME FAST scoring with p = 0.024. From the 2x2 table calculations, the sensitivity of the HOME FAST adaptation scoring method was low with 46% and the specificity of 67%. Conclusion: The adaptation of HOME FAST has a sensitivity of 46% and a specificity of 67%. The prevalence of adaptation results from HOME FAST risk of falling was 36.66%, with the number of safe houses were 190 housing units and 110 unsafe houses.